2017
DOI: 10.1016/j.kontakt.2017.09.010
|View full text |Cite
|
Sign up to set email alerts
|

The "Heretic" debate on European asylum quotas in the Czech Republic: A content analysis

Abstract: This article examines the Czech political scene, by focusing on the attitude of the main political parties in the Czech Republic and their attitude towards the issue of migration quotas in the period between May 2015 and July 2017. It touches upon the migration quota issue by, first of all, shortly describing main characteristics of Czech political parties in terms of European integration in general and additionally by discussing the modes in which Czech political parties comprehended the migration quota issue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…In such discourse, critiques often point to the lack of appropriate security measures or express displeasure with 'refugee quotas', which serve as a pull factor for migration (Braun, 2020). In the Czech case, the privileged position of the quota system is logical; indeed, it has been the key agenda for Czech political parties across the party scene (Hrabálek & Đorđević, 2017). In sum, within this discourse, input and throughput legitimacy is questioned; meanwhile, security-oriented output legitimacy is desirable.…”
Section: Discussionmentioning
confidence: 99%
“…In such discourse, critiques often point to the lack of appropriate security measures or express displeasure with 'refugee quotas', which serve as a pull factor for migration (Braun, 2020). In the Czech case, the privileged position of the quota system is logical; indeed, it has been the key agenda for Czech political parties across the party scene (Hrabálek & Đorđević, 2017). In sum, within this discourse, input and throughput legitimacy is questioned; meanwhile, security-oriented output legitimacy is desirable.…”
Section: Discussionmentioning
confidence: 99%
“…None of our respondents had immigrant as a friend or at the classroom. Therefore, their fear could be the fear of unknown or fear fed by the images presented by the media at the time of data collection, emphasizing security risks and rejection of the quota system proposed by European Union (beginning of the refugee influx in summer 2015; Hrabálek & Đorđević, ; Tkaczyk, Pospěch, & Macek, ). Considering recent meta‐analysis that has shown that the effects of both direct and indirect contact are successful in prejudice reduction and tend to last over the time (Lemmer & Wagner, ) and study focused on effects of negative contact (Barlow et al., ), we cannot omit the possible influence media had in shaping our respondents’ opinions.…”
Section: Discussionmentioning
confidence: 99%
“… ** Lawsuit—whether Czech Republic should engage in legal action against refugee quotas proposed by European Union (Hrabálek & Đorđević, ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations